Effect of excimer laser annealing on a-InGaZnO thin-film transistors passivated by solution-processed hybrid passivation layers. (22nd December 2015) - Bermundo, Juan Paolo; Ishikawa, Yasuaki; Fujii, Mami N; Nonaka, Toshiaki; Ishihara, Ryoichi; Ikenoue, Hiroshi; Uraoka, Yukiharu
Abstract: We demonstrate the use of excimer laser annealing (ELA) as a low temperature annealing alternative to anneal amorphous InGaZnO ( a -IGZO) thin-film transistors (TFTs) passivated by a solution-processed hybrid passivation layer. Usually, a -IGZO is annealed using thermal annealing at high temperatures of up to 400 °C. As an alternative to high temperature thermal annealing, two types of ELA, XeCl (308 nm) and KrF (248 nm) ELA, are introduced. Both ELA types enhanced the electrical characteristics of a -IGZO TFTs leading to a mobility improvement of 13 cm 2 V −1 s −1 and small threshold voltage which varied from 0–3 V. Furthermore, two-dimensional heat simulation using COMSOL Multiphysics was used to identify possible degradation sites, analyse laser heat localization, and confirm that the substrate temperature is below 50 °C. The two-dimensional heat simulation showed that the substrate temperature remained at very low temperatures, less than 30 °C, during ELA. This implies that any flexible material can be used as the substrate. These results demonstrate the large potential of ELA as a low temperature annealing alternative for already-passivated a -IGZO TFTs.